Micropillar substrates: A tool for studying cell mechanobiology - Gupta, Mukund; Kocgozlu, Leyla; Sarangi, Bibhu Ranjan; Margadant, Felix; Ashraf, Mohammed; Ladoux, Benoît (Academic Press Inc., 2015)
Increasing evidence has shown that mechanical cues from the environment play an important role in cell biology. Mechanotransduction or the study of how cells can sense these mechanical cues, and respond to them, is an active field of research. However, it is still not clear how cells sense and respond to mechanical cues. Thus, new tools are being rapidly developed to quantitatively study cell mechanobiology. Particularly, force measurement tools such as micropillar substrates have provided new insights into the underlying mechanisms of mechanosensing. In this chapter, we provide detailed protocol for fabrication, characterization, functionalization, and use of the micropillar substrates.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Force measurement; Mechanotransduction; Micropillar substrates; Rigidity; Traction force microscopy